Innovation Typology of the Local Government in Educational Affairs - Abdullah, Muh Tang; Supriyono, Bambang; Muluk, M.R Khairul; Tjahjanulin, Tjahjanulin (UI Scholars Hub, 2018)
Many studies have been carried out on the application of innovation concept in the local government administration, but none has specifically studied innovation typology from the aspect of levels and types of the innovations developed. Therefore, it is important to understand the innovation typology developed by the local government. This study focuses on the development of innovative program of the local government in educational affairs. Through descriptive-qualitative method, this study aims to describe innovation typology of educational affairs. Primary data is obtained from interviews and field observations while secondary data is obtained from official documents of the local government. The data are analyzed with Spiral Model technique. The findings show four programs of innovation, namely Educational Studio of Pious Children (SPAS), Free Education, Punggawa D'Emba Education Program (PDEP), and Task Force for Education. They are categorized as innovation typology of the process of service at the incremental level adopted from other regions through a replication strategy.